Applying Lithogeochemical Discrimination Tools for Nickel-Copper Sulfide Exploration in Northern Finland : A Case study of First Quantum Minerals Exploration Targets - Chamanifard, Emad (2013)
The Kevitsa-Satovaara complex is a mafic-ultramafic intrusion of age 2.05 Ga located in Central Lapland Greenstoe Belt. The discovery of the Kevitsa ore mine resulted in opening the mine by First Quantum Minerals Ltd. (FQM) in 2012. Area has been under active exploration from 1990’s and number of smaller intrusions have been studied by geophysics, drilling and till sampling. Total number of 4220 samples of Kevitsa mine and 20 exploration targets and were selected from the database. The purpose of this research is to take a closer look on the new exploration targets by new geochemical tools.Only a few elements were required for the geochemical tools used in this research: The rock forming elements Si, Al, Ca, K, Na, Ti, Fe, Mg and ore elements, Ni, Cu, Co, S. All the samples were analyzed by ICPMS methods and for less than 10% includes XRF analysis. Si is missing for more than 90% of samples which is modeled by a linear regression modeling and other elements.Two new parameters were calculated from sulfide cumulates which are useful in monitoring sulfide segregation of magma. The Co#, 100*Co/(Co+Ni+Cu), shows the depletion of magma from Ni, and the Ni#, 100*Ni/(Ni+Cu), which shows the primitiveness of magma. In all targets except Ponostama, Co# number is very low (less than 7) which show an undepleted magma. For a few targets Ni# shows a komatiitic or combination of komatiitic and picritic composition with very high (90-100) Ni#. Also there is a trend toward the zero point of the Ni#-Co# graph which is very important in an economic Ni mineralization.A new lithogeochemical test was developed by Lamberg (2005) for identification of fertile intrusion called fertility analysis. There are seven parameters in this analysis which quantifies all the evolution of magma toward an economic Ni mineralization. The Overall Discrimination value or OD value is then calculated by these parameters. OD value is range from 0.00 7.49 that shows how many steps the target passed. All FQM exploration targets and Kevitsa mine were tested ...